LITERASI KEUANGAN DAN MANAJEMEN KEUANGAN PRIBADI MAHASISWA DI PROVINSI BENGKULU - Chairil Afandy; Febrilianty Fransiska Niangsih (UNIB Press, 2020)
This study aims to describe and reveal the effect of financial literacy on the personal financial management of college students in the Province of Bengkulu. The population in this study was all college students in the Province of Bengkulu, with 339 as respondents. The sampling technique used in this research is quota sampling. The data used in the study are primary data obtained through online questionnaires. This research shows that college students in the Province of Bengkulu tend to have low financial literacy levels. While this study also found that college students' personal financial management in Bengkulu Province could be said to be good. The result reveals that financial literacy affects personal finance management among college students in the Province of Bengkulu.